2018
DOI: 10.1159/000481173
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Triple Endoscopy Improves Clinical Staging of Primary Head and Neck Cancer

Abstract: Background: Correct pre-therapeutic staging of the first primary carcinoma (FPC) and detection of simultaneous second primary carcinomas (SSPCs) decisively influence therapy and prognosis of head and neck squamous cell carcinomas (HNSCC). The aim of this study was to determine the benefit of pre-therapeutic triple endoscopy for detection of SSPC and pre-therapeutic T category. Methods: A cohort of 234 HNSCC patients with completed triple endoscopy was reviewed, focusing on pre-therapeutic T category and SSPC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…After the first 5 years, the patient continues follow‐up once per year with a clinical visit, regardless of subsite cancer and stage at diagnosis or treatments received. Several studies evaluated the role of triple endoscopy in this setting, especially in pre‐treated work‐up to diagnosticate the synchronous SPT (Krishnatreya et al., 2015; Priante et al., 2014; Sharma et al., 2018). However, most reports only describe the frequency of diagnoses and not the benefit on survival of these patients (Priante et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…After the first 5 years, the patient continues follow‐up once per year with a clinical visit, regardless of subsite cancer and stage at diagnosis or treatments received. Several studies evaluated the role of triple endoscopy in this setting, especially in pre‐treated work‐up to diagnosticate the synchronous SPT (Krishnatreya et al., 2015; Priante et al., 2014; Sharma et al., 2018). However, most reports only describe the frequency of diagnoses and not the benefit on survival of these patients (Priante et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Wang 15 Sharma et al demonstrated that SSPL prevalence was 5.56% (13 SSPL/234 HNSCC) and only 3 (23.13%) of 13 of SSPLs were exclusively found by triple endoscopy (direct laryngoscopy, bronchoscopy, and esophagoscopy). 16 However, other authors believed that endoscopic screening has a low yield and do not recommend it for concurrent use with other imaging modalities. 10,17 Additionally, some studies suggested that the incidences of SSPL in HNSCC were low.…”
Section: Discussionmentioning
confidence: 99%
“…Die Änderungen wurden also maßgeblich unter dem Aspekt der rein prognostischen Bedeutung für das Überleben der Patienten durchgeführt. Man muss also bei der Betrachtung von Tumorstadien sehr darauf achten, insbesondere bei paralleler Tabak-, Alkohol-und HPV-Assoziation, nicht in die Gefahr des "Undertreatments", einer unangemessen reduzierten Therapieintensität, zu geraten [61,62,63].…”
Section: Kl Assifik Ation Die 8 Edition Der Tnm-klassifikation (Uicc ...unclassified